Defense against Reactive Carbonyl Species Involves at Least Three Subcellular Compartments Where Individual Components of the System Respond to Cellular Sugar Status. Issue 12 (17th November 2017) - Schmitz, Jessica; Dittmar, Isabell C.; Brockmann, Jörn D.; Schmidt, Marc; Hüdig, Meike; Rossoni, Alessandro W.; Maurino, Veronica G.
Abstract : Detoxification of reactive carbonyl species produced by enhanced cellular sugar levels involves at least three subcellular compartments and depends on a specific glyoxalase I isoform during germination. Abstract: Methylglyoxal (MGO) and glyoxal (GO) are toxic reactive carbonyl species generated as by-products of glycolysis. The pre-emption pathway for detoxification of these products, the glyoxalase (GLX) system, involves two consecutive reactions catalyzed by GLXI and GLXII. In Arabidopsis thaliana, the GLX system is encoded by three homologs of GLXI and three homologs of GLXII, from which several predicted GLXI and GLXII isoforms can be derived through alternative splicing. We identified the physiologically relevant splice forms using sequencing data and demonstrated that the resulting isoforms have different subcellular localizations. All three GLXI homologs are functional in vivo, as they complemented a yeast GLXI loss-of-function mutant. Efficient MGO and GO detoxification can be controlled by a switch in metal cofactor usage. MGO formation is closely connected to the flux through glycolysis and through the Calvin Benson cycle; accordingly, expression analysis indicated that GLXI is transcriptionally regulated by endogenous sugar levels. Analyses of Arabidopsis loss-of-function lines revealed that the elimination of toxic reactive carbonyl species during germination and seedling establishment depends on the activity of the cytosolic GLXI;3 isoform. The Arabidopsis GLX system involves the cytosol, chloroplasts, and mitochondria, which harbor individual components that might be used at specific developmental stages and respond differentially to cellular sugar status.